Determinants of foreign direct investment revisited in a regiocentric environment. (16th January 2009) - Anwar, Syed Aziz
In view of the economic integration process taking place with considerable speed in the six oil-rich Gulf Co-operation Council (GCC) countries, the question of attracting foreign direct investment (FDI) has come into sharper focus. In fact, policymakers in some of these countries consider FDI inflows as an index of the success of their international business regimes. This paper examines and analyses the evidence pertaining to FDI in the GCC region. It is argued that the process of economic co operation and integration leading to the formation of a customs union in 2003 in the GCC countries has the potential to enhance the attractiveness of these nations for FDI inflows. Based on a survey exercise, the paper goes on to identify the perceived regiocentric determinants of FDI in the context of economic integration in the GCC region. While most of the determinants identified in the paper are in line with conventional wisdom, it is argued that their hierarchical importance is context-specific.